Structural rejuvenation in bulk metallic glasses. (March 2015) - Tong, Y.; Iwashita, T.; Dmowski, W.; Bei, H.; Yokoyama, Y.; Egami, T.
Abstract: Using high-energy X-ray diffraction we study structural changes in bulk metallic glasses after uniaxial compressive homogeneous deformation at temperatures slightly below the glass transition. We observe that deformation results in structural disordering corresponding to an increase in the fictive, or effective, temperature. However, the structural disordering saturates after yielding. Examination of the experimental structure and molecular dynamics simulation suggests that local changes in the atomic connectivity network are the main driving force of the structural rejuvenation.